Structural Protein Requirements in Equine Arteritis Virus Assembly - Wieringa, Roeland (American Society for Microbiology, 2004)
Equine arteritis virus (EAV) is an enveloped, positive-stranded RNA virus belonging to the family Arteriviridae of the order Nidovirales. EAV particles contain seven structural proteins: the nucleocapsid protein N, the unglycosylated envelope proteins M and E, and the N-glycosylated membrane proteins GP(2b) (previously named G(S)), GP(3), GP(4), and GP(5) (previously named G(L)). Proteins N, M, and GP(5) are major virion components, E occurs in virus particles in intermediate amounts, and GP(4), GP(3), and GP(2b) are minor structural proteins. The M and GP(5) proteins occur in virus particles as disulfide-linked heterodimers while the GP(4), GP(3), and GP(2b) proteins are incorporated into virions as a heterotrimeric complex. Here, we studied the effect on virus assembly of inactivating the structural protein genes one by one in the context of a (full-length) EAV cDNA clone. It appeared that the three major structural proteins are essential for particle formation, while the other four virion proteins are dispensable. When one of the GP(2b), GP(3), or GP(4) proteins was missing, the incorporation of the remaining two minor envelope glycoproteins was completely blocked while that of the E protein was greatly reduced. The absence of E entirely prevented the incorporation of the GP(2b), GP(3), and GP(4) proteins into viral particles. EAV particles lacking GP(2b), GP(3), GP(4), and E did not markedly differ from wild-type virions in buoyant density, major structural protein composition, electron microscopic appearance, and genomic RNA content. On the basis of these results, we propose a model for the EAV particle in which the GP(2b)/GP(3)/GP(4) heterotrimers are positioned, in association with a defined number of E molecules, above the vertices of the putatively icosahedral nucleocapsid.